An adaptation of the dual-affine interior point method for the surface flatness problem - Balbo, Antonio Roberto [UNESP]; Baptista, Edméa Cássia [UNESP]; Arenales, Marcos Nereu (Elsevier B.V., 2007)
This paper presents an adaptation of the dual-affine interior point method for the surface flatness problem. In order to determine how flat a surface is, one should find two parallel planes so that the surface is between them and they are as close together as possible. This problem is equivalent to the problem of solving inconsistent linear systems in terms of Tchebyshev's norm. An algorithm is proposed and results are presented and compared with others published in the literature. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: interior point methods; linear programming; surface flatness problem; Tchebyshev's norm